Effectiveness of a Training Program to Enhance Clinical Supervision of State Vocational Rehabilitation Personnel. (October 2018) - Herbert, James T.; Schultz, Jared C.; Lei, Puiwa; Aydemir-Döke, Deniz
A training program to improve clinical supervision behavior, knowledge, self-efficacy, and working alliance among state vocational rehabilitation supervisors (SVRS) was studied. SVRS ( n = 180) were randomly assigned to either the control or experimental group. To further validate training effectiveness, counselors ( n = 350) who were assigned to both groups of supervisors also completed parallel outcome measures evaluating their supervisors' performance. Results indicate differential impact when comparing changes across baseline, Posttest 1 (approximately 6 weeks after baseline), and Posttest 2 data collection (approximately 6 months after baseline) between both supervisory groups. Specifically, in comparison with the control group, supervisors who received the training reported greater changes at Posttest 1 regarding time spent in individual supervision, frequency, and time devoted to group supervision as well as perceived value in providing clinical supervision. Posttest 2 evaluation between groups noted differences in clinical supervision knowledge and behavior, frequency of individual supervision sessions, and time spent in group supervision. In contrast, counselors assigned to one of the supervisory groups reported few differences in parallel outcome measures. Although the intervention provided some support for its effectiveness for supervisors, further modifications are needed before a valid training model exists for rehabilitation counseling.